Participação do tronco na cinética e nos fluxos de energia do membro inferior de balanço durante o chute no futebol: um estudo descritivo - Diego da Silva Carvalho (2017)
Introduction: It is possible that the trunk (thorax and abdomen) and the musculoskeletal soft tissues that connect the trunk to the pelvis participate in the mechanics of soccer kick, with kinetic energy transfers to the lower limb. In an extensive search in the literature was not found a description of the kinetic role of the trunk during the gesture. Thus, the objective of this study was to estimate the moments and powers involving the trunk, the pelvis, segments of the lower limbs and the joints thorax-abdomen, waist, both hips, knees and ankles to describe the participation of the trunk in the flows of mechanical energy of the lower swing limb during the soccer kick. Materials and Method: A cross-sectional observational study was performed with eighteen amateur soccer players (age 24 ± 4.1 years). Participants were instructed to kick a soccer ball with the dorsum of the foot of the dominant lower limb "as strong as possible" in the direction of a rectangular target. The kinematic and inertial data were used to calculate the joint moments using the inverse dynamics method. An energy flow analysis with power calculations was performed to estimate how kinetic energy changes involving the segments and the joints. The angular curves of kinematics, moments and segmental and articular powers were presented individually and mean curves were generated. From the curves, they were described as directions of the kinetic energy flows, to reveal the kinetic role of the upper and lower trunks during the kick. Results and Discussion: The trunk has a kinetic contribution of 23% (thorax-abdomen = 11% and waist = 12%) for movements of the lower swing limb during the kick. The trunk is exploited by the motor system in the initial phases of the gesture to generate energy flows in the lower sense favoring the posterior inclinations of the segments of the lower swing limb, accompanied by the anterior linear displacement of the limb towards the ball. The results corroborate a presence of a dynamic similar to a "tensional arc" in the waist and hip joints and a large "segmented pendulum" whose upper segments (trunk) are inclined posteriorly to lead to the same angular movement of the lower segments, subsequently. In addition, the hip of the lower support limb contributes significantly to a flow of energy related to the production of the pelvic movement that participates in the ball reach. In subsequent phases, the trunk joints also participate in the withdrawal of energy from the body segments. Conclusion: The present study demonstrates a presence of a dynamic similar to a "tensional arc" in the waist and hip joints, and a large "segmented pendulum" whose upper segments are inclined posteriorly to lead to the same angular movement of the lower segments, subsequently. These descriptions provide the opportunity to explore possible theoretical and practical implications of the demands of stress that can lead to typical kicking injuries and the consideration in clinical practice of upper body with the goals of preventing and / or treating musculoskeletal injuries.